Examining Extension-Supported Rural Community Coalitions During COVID-19 - Catherine Jones; Abigail Borron; Alexa Lamm; Catherine Dobbins; Ellen Farmer; Marsha Davis (Journal of International Agricultural and Extension Education, 2021)
Key informant interviews with extension-supported community coalition members in five rural communities during the COVID-19 pandemic were used to examine the unique characteristics of rural community resiliency in the face of a crisis based onthe community capitals framework. Using a thematic analysis, seven different human and material capitals were examined in community members’ reactions to a “black swan” event. Rural community coalition members shared their perspectives on the vitality of their community in the face of adversity which revealed obstacles extension professionals can support through community development efforts focused on building resiliency. The analysis identified three emergent themes: (1) juxtaposing restrictions and uncertainties with unexpected successes; (2) demonstrating resiliency through connectedness; and (3) correlating community health with changing perceptions of COVID-19. Additionally, each theme was juxtaposed with the interplay of community capitals as they related to coalition efforts in a pandemic that can assist if further developing health communication and extension education efforts within rural communities across the globe in times of crisis
Keywords: rural; resiliency; Community Capitals Framework; health communication; COVID-19